Bibliometric Analysis of Child Protection Policy Performance in Southeast Asia - Khalil, Zakki Fuad; Marzaniar, Putri; Ratnawati, Ratnawati; Zamharira, Cut; Muazzinah, Muazzinah (El-Usrah: Jurnal Hukum Keluarga, 2025)
Children's issues are a matter of significant public concern, especially given their crucial role as the nation's next generation. As valuable national assets, children possess numerous rights that their countries must guarantee. This research aims to analyze child protection policies in ASEAN countries through a systematic literature review. The data synthesis process involved comparing 60 articles that met stringent quality assessment, inclusion, and exclusion criteria. The data was subsequently processed and presented in tabulated form. The results revealed various forms of violence against children prevalent in the ASEAN region, including sexual, domestic, and cyber violence, exploitation, and neglect. Furthermore, the nodality model is the most dominant child protection policy formulation model adopted by ASEAN countries, primarily focusing on law enforcement and the fulfillment of children's rights. However, existing policies are more oriented toward handling cases after children become victims rather than prioritizing preventive efforts. Most notably, while conventional policies often focus solely on children's rights post-birth, a compelling multi-area perspective emerges from Islamic teachings. These teachings comprehensively regulate child protection starting even before birth, through pre-marital guidance and pregnancy preparation, extending to the parenting stages with a strong emphasis on moral and spiritual character development, and encompassing the entire spectrum of formal and informal child education. This finding highlights a critical gap in child protection within the ASEAN region, underscoring the urgent need to strengthen preventive measures. This research is expected to contribute to the development of more comprehensive and effective child protection policies across the ASEAN region, potentially integrating these holistic Islamic principles.